2010
DOI: 10.1089/vim.2010.0014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-HPV11-L1 Antibodies in Immune Sera from Patients Suffering from Recurrent Respiratory Papillomatosis Using ELISA

Abstract: CitationDetection of anti-HPV11-L1 antibodies in immune sera from patients suffering from recurrent respiratory papillomatosis using ELISA. Infection with human papillomaviruses (mostly HPV6 and HPV11) may lead to recurrent respiratory papillomatosis (RRP), a chronic disease affecting 2-4/100,000 people. Papillomas have to be removed surgically so patients can breathe normally. Papillomas often grow back and some patients are subjected to a number of operations. In general, asymptomatic HPV-positive people hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
2
1
Order By: Relevance
“…In the study by Buchinsky et al, almost half (47%) of adult and adolescent participants with a median (range) duration of symptoms of 11 (1-69) years possessed no antibodies against HPV-6 and HPV-11. The proportion of seropositive people with RRP according to some studies may be positively correlated with the duration of symptomatic disease and the number of surgery-necessitating interventions . The duration of the disease before enrollment was slightly shorter in our study in comparison with that of Buchinsky et al, so the higher percentage of seropositive patients may be more likely attributable to the use of diverse methods for antibody level testing.…”
Section: Discussioncontrasting
confidence: 43%
“…In the study by Buchinsky et al, almost half (47%) of adult and adolescent participants with a median (range) duration of symptoms of 11 (1-69) years possessed no antibodies against HPV-6 and HPV-11. The proportion of seropositive people with RRP according to some studies may be positively correlated with the duration of symptomatic disease and the number of surgery-necessitating interventions . The duration of the disease before enrollment was slightly shorter in our study in comparison with that of Buchinsky et al, so the higher percentage of seropositive patients may be more likely attributable to the use of diverse methods for antibody level testing.…”
Section: Discussioncontrasting
confidence: 43%
“…In our concurrent study, HPV-6 genotype has been identified in 30% cases of juvenile-onset recurrent respiratory papillomatosis among 47 patients investigated (3–12 year old) [6]. Concordant results concerning high HPV-11 prevalence in normal oral mucosa were not reported in literature.…”
Section: Discussionmentioning
confidence: 85%
“…Duration and surgical count correlated with seronegative vs seropositive but not with titre given seropositivity. We were thus surprised when Durzyńska et al [25] reported a very tight correlation between ELISA absorbance and surgical count; an extraordinary 87% of the variance in absorbance could be predicted by the variance in surgical count. They only tested anti-HPV11 and 30% of their 47 subjects were not infected with HPV11.…”
Section: Plos Onementioning
confidence: 95%